Various Techniques for Molecular and Rapid Detection of Infectious and Epidemic Diseases - Shahrajabian, Mohamad H.; Sun, Wenli (Letters in Organic Chemistry, 2023)
Polymerase chain reaction is an approach to make numerous copies of specific DNA. PCR has been applied for the investigation of infectious sicknesses caused by viral, protozoan, bacterial, fungal, or other infectious factors. This review manuscript aims to survey the usage of PCR, LAMP, RPA, and RAA in rapid detection and highlight molecular detection of various diseases and pathogens. Scientific sources like Science Direct, PubMed, Research gate, Scopus, and Google Scholar with highlighting on Science Direct and Scopus have been applied. A review of the literature was prepared by using the keywords PCR, LAMP, infectious disease, pathogen, RAA, RPA, and virus. Loop-mediated isothermal amplification (LAMP) is a nucleic acid amplification method presenting the substitute to PCR. The LAMP assay is more rapid than nested PCR, is cost-efficient, and is simple to perform. LAMP technology has been widely used for the detection of crop pests, human pathogenic, pathogenic, organisms, bacteria, and components in meat products. Recombinase polymerase amplification (RPA) is a new isothermal technique to amplify the DNA as well as RPA. RPA combined the advantages of isothermal PCR with clarity and rapid amplification. Recombinase- aided amplification (RAA) assay has been successfully applied in the detection of bacterial and viral pathogens and controls the technical problems posed by DNA amplification techniques because it does not require thermal denaturation of the template and utilizes at a debilitated and continuous temperature. This manuscript has highlighted the importance of PCR and molecular detection as significant tools in the detection of infectious organisms, pathogens, toxins, and biological research.
Keywords: RPA